Concise semisynthesis of novel phenazine-vitamin E hybrids via regioselective tocopheryl ortho-quinone formation. Issue 27 (4th July 2018) - Viault, Guillaume; Helesbeux, Jean-Jacques; Richomme, Pascal; Séraphin, Denis
Graphical abstract: Highlights: Concise semisynthetic route to phenazine-vitamin E hybrids. IBX regio and chemoselective oxidation in vitamin E series. Efficient IBX mediated tocopheryl ortho -quinone formation. Abstract: A regioselective method for the semisynthesis of phenazine derivatives has been disclosed through an efficient IBX mediated ortho -quinone formation from vitamin E derivatives. High chemo- and regio-selectivity was observed during the oxidation step and the corresponding 5, 6- ortho -quinones could react with various phenylenediamines. Thus, this methodology proves its interest as a concise semisynthetic pathway to phenazine-vitamin E hybrids with moderate to good yields.